Investigation of Experimental Devices for Finger Active and Passive Tactile Friction Analysis - Zhou, Xue; Masen, Marc A.; Mo, Jiliang; Shi, Xinyu; He, Yaosheng; Jin, Zhongmin (Chinese journal of mechanical engineering, 2023)
Complicated tribological behavior occurs when human fingers touch and perceive the surfaces of objects. In this process, people use their exploration style with different conditions, such as contact load, sliding speed, sliding direction, and angle of orientation between fingers and object surface consciously or unconsciously. This work addressed interlaboratory experimental devices for finger active and passive tactile friction analysis, showing two types of finger movement. In active sliding experiment, the participant slid their finger freely against the object surface, requiring the subject to control the motion conditions themselves. For passive sliding experiments, these motion conditions were adjusted by the device. Several analysis parameters, such as contact force, vibration acceleration signals, vibration magnitude, and fingerprint deformation were recorded simultaneously. Noticeable friction differences were observed when comparing active sliding and passive sliding. For passive sliding, stick-slip behavior occurred when sliding in the distal direction, evidenced by observing the friction force and the related deformation of the fingerprint ridges. The employed devices showed good repeatability and high reliability, which enriched the design of the experimental platform and provided guidance to the standardization research in the field of tactile friction.